Quantitative method developing hydrogen standard sample for GDOES - Qingyang Liu; Sumia Manzoor; Yan Yan; Mohammad Tariq; Hanan Farhat; Afrooz Barnoush (Materials Letters: X)
This present study investigates the measurement of the hydrogen concentration and gradient on the surface of hydrogen charged samples using Glow Discharge Optical Emission Spectroscopy (GDOES). Hydrogen measurement from GDOES suffers from atmospheric contaminations at the beginning of each measurement and hydrogen desorption on the surface also reduces the credibility of measurement. Another shortcoming is there is no calibration sample for GDOES with a known amount of hydrogen. We addressed these challenges by coating the sample with a reproducible and reliable Ni layer right after hydrogen charging. Results demonstrate a strong correlation between hydrogen intensity measured by GDOES on the deposited Ni layer and hydrogen amounts measured by thermal desorption spectroscopy (TDS) analysis. This correlation is a groundbreaking step toward developing calibration samples for hydrogen measurement. In this work, the hydrogen measurement validation of GDOES using TDS by examining hydrogen on hydrogen charged samples is presented.